Orbital and optic pathway sarcoidosis: MR findings. - Carmody, R F; Mafee, M F; Goodwin, J A; Small, K; Haery, C (American Journal of Neuroradiology, 1994)
PURPOSE To identify and characterize the MR findings of sarcoidosis when it involves the orbit and visual pathways. METHODS The MR scans of 15 patients, 3 with presumed and 12 with proved orbital or optic pathway sarcoidosis were retrospectively reviewed. RESULTS Eight patients had MR evidence of optic nerve involvement by sarcoid granuloma. Perineural enhancement was seen in four cases, optic atrophy in one. Three who had had unenhanced scans showed optic nerve enlargement. Nine patients had optic chiasmal involvement. One patient had increased T2 signal in the optic radiations. Three patients had orbital masses that had MR signal characteristics similar to pseudotumor. Five patients had periventricular white matter abnormalities closely resembling multiple sclerosis. CONCLUSIONS Sarcoidosis should be considered in the differential diagnosis of optic nerve or nerve sheath enhancement on MR. Orbital sarcoidosis has MR characteristics very similar to pseudotumor.